Enhancing Student Services at Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial: A SWOT Analysis - Putranto, Diyan; Frans Amonio, Halawa; Rintis Eko , Widodo; Due, Laurensius Reinald Diansilves; Siagian, Kartini; Wati, Mirna (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the student service system at the Lentera Mondial College of Tourism and Logistics Management using qualitative methods and SWOT analysis. This research identifies strengths, weaknesses, opportunities, and threats to improve student satisfaction and academic experience. Key findings include comprehensive academic support, technology integration, culturally responsive services, and alignment with industry. However, there are limitations in accessibility, communication gaps, resource constraints, and obstacles in seeking support. Recommendations include digital bridges, strengthening communications, and optimizing resource allocation to improve student services and overall satisfaction.